Semen characteristics, semen discard rate and fertility in Murrah buffalo bulls - KANCHAN,; SINGH, NARINDER (The Indian Journal of Animal Reproduction, 2023)
A total of 2747 collections from 24 buffalo bulls were evaluated to find the per cent semen discard at the time of semencollection and also during freezing process. Bulls were categorized into three semen discard groups; low (30-50%), medium (50-70%)and high (70-90% ). The various parameters viz. age at first collection, body weight at first collection, average semen volume, preand post-freezing discard, initial motility, post-thaw motility and conception rate were studied among these groups to find the effectof di scard rate on fe rtility of Murrah buffalo bulls. The mean values of various parameters viz. age at first collection (months), bodyweight at first collection (kg), average semen volume (ml), pre-freezing discard (%) and post-freezing discard (% ), initial motility(%), post-thaw motility (%) and conception rate (%) were 27.2±1.37, 386.50±21.06; 3.47±0.14, 32.41±2.87, 29.30±2.26,57.37:tl.06, 42.71±0.81 and 29.36±2.15, respectively. The results have shown that the age and weight of bulls at sexual maturitywere lowest in high semen discard group (22.9±2.88 months and 347.5±45.17 kg). The mean value of age and body weight at firstcollection, average semen volume, pre-freezing semen discard and conception rate did not vary significantly among three discardgroups. The results indicate that conception rate of bulls is not effected by discard rate of semen. Post-freezing discard wassignificantly higher (Ps().01) in high discard group as compared to other discard groups. Initial motility and post-thaw motility ofsemen was signifo.antly higher (Ps().01; P~0.05) in low discard group as compared to medium and high discard groups. The resultsindicated that the studies on semen discard rate would help to identify bulls with minimum discard rate with best semen characteristicsfor selection in breeding programme to meet the semen production targets for genetic improvement of this species.
Keywords: Semen characteristics; discard rate; fertility; Murrah buffalo bull